Преобразовать в многочлен стандартного вида выражение: а) x²-3x+2-2x b) (2x-1)x c) 5x²(-x²+2x-3) d) (x+4)(x²-4x+16)

Преобразовать в многочлен стандартного вида выражение: а) x²-3x+2-2x b) (2x-1)x c) 5x²(-x²+2x-3) d) (x+4)(x²-4x+16)
Гость
Ответ(ы) на вопрос:
Гость
[latex]1) x^2-3x+2-2x= x^{2} -5x+2 \\ 2)(2x-1)x=2 x^{2} -x \\ 3)5 x^{2} (- x^{2} +2x-3)=-5 x^{4} +10 x^{3} -15 x^{2} \\ 4)(x+4)( x^{2} -4x+16)= x^{3}-4 x^{2} +16x+4 x^{2} -16x+64= x^{3} +64 [/latex]
Гость
A)х^-5х+2 Б)2х^-х С)-5х4+10х3-15х^ D)x3+64
Не нашли ответ?
Ответить на вопрос
Похожие вопросы